An Empirical Study of Bonds as a Safe Haven in Indonesia During COVID-19 and Russia-Ukraine War - Fahmi Ihwanul Arifin; Robiyanto Robiyanto; Yefta Andi Kus Noegroho; Harijono Harijono (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2026)
This study examines whether government and corporate bonds in Indonesia act as hedging or safe haven assets during the COVID-19 pandemic and the Russia–Ukraine war. This study using data started from March 3, 2020 which is the date of the first Covid-19 case emerged in Indonesia to March 29, 2024 even though the war is not over yet on the time this study being conducted. The cut-off date for the Russia-Ukraine war is February 24, 2022. Generalized Autoregressive Conditional Heteroskedasticity (GARCH) is used in order to test the potential of bonds as hedges, while QREG used in order to test the potential of bond as safe haven. The findings show that during the period of financial and geopolitical crisis, Indonesian government and corporate bonds cannot be an effective safe haven or hedge against the stock market. While they can serve as diversification assets due to their stable volatility, these bonds lack the consistent negative correlation with the Composite Stock Price Index (CSPI) required for safe haven assets. Investors and portfolio managers should be cautious in relying on government bonds and corporate bonds as hedge against stock market declines. The results suggest that bonds may not provide the expected protection against stock market declines, so investors need to consider alternative diversification strategies or other hedging instruments when making investment decisions.